Kandungan Asam Amino Tempe Kedelai Lokal Indonesia dan Tempe Kedelai Impor - Widiany, Fery Lusviana; Metty, Metty; Widaryanti, Rahayu; Azizah, Shafira Nur (ARGIPA (Arsip Gizi dan Pangan), 2023)
Tempeh can potentially be used as a functional food, because it has high nutritional content. The types of tempeh sold on the Indonesian market include local soybean tempeh and imported soybean tempeh. Many people do not understand the differences between these two types of tempeh. This research was conducted to analyze the differences in amino acid content in local soybean tempeh and imported soybean tempeh. This experimental research was carried out in 2022 at the Dietetics and Culinary Laboratory at Respati University, Yogyakarta and the Saraswanti Laboratory, Bogor, Indonesia. The independent variable was variation of local soybean tempeh and imported soybean tempeh, while the dependent variable was amino acid content. Data were statistically analyzed using the Independent T-Test. The results of the analysis of the differences in amino acid content of local soybean tempeh and imported soybean tempeh for all types of amino acids showed a p-value <0.05. Methionine as a limiting amino acid in local soybean tempeh and imported soybean tempeh. In conclusion, there is a significant difference in amino acid levels between local soybean tempeh and imported soybean tempeh.